Impact of age and pre-existing immunity on the induction of human antibody responses against influenza B viruses. Issue 9 (2nd September 2019) - Carlock, Michael A.; Ingram, John G.; Clutter, Emily F.; Cecil, Noah C.; Ramgopal, Moti; Zimmerman, Richard K.; Warren, William; Kleanthous, Harry; Ross, Ted M.
ABSTRACT: Pre-existing immunity to influenza is dependent on a number of factors and can vary greatly within and across influenza subtypes. In this study, volunteers (aged 18–85 years) were vaccinated with split, inactivated Fluzone TM in four consecutive influenza seasons from 2013 to 2016. The impact of repeat vaccination on breadth and durability of functional antibodies was assessed for total IgG and IgA anti-hemagglutinin (HA) binding antibodies and hemagglutination-inhibition (HAI) activity against both influenza B lineages. Many subjects were able to maintain high seroprotective titers to the vaccine strains in subsequent years, which resulted in low vaccine-induced seroconversion rates. This was especially evident in younger subjects who typically had higher titers and maintained these titers into the following season. In contrast, the HAI titers in elderly subjects were generally lower and more likely to decline prior to the start of the next influenza season. Immunological recall or 'back-boosting' to antigenically related viruses was associated with seroconversion. Overall, influenza vaccination in both younger and older people elicited broadly reactive immune responses within a lineage, as well as cross-reactive immune responses between lineages. This study exemplified the impact that age and influenza exposure history have on determining an individual's ability to respond to future influenza infections.